Development of Quick Count Math Educational Game–Based Media for Learning Integers - Mangamis, Freiti; Tilaar, Anetha L.F.; Sumarauw, Sylvia J.A. (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
In response to students’ persistent difficulties in understanding integer operations and the limited use of engaging digital game-based media in mathematics classrooms, this study aims to develop “Quick Count Math,” an educational game-based instructional medium on the topic of integers for seventh-grade junior high school students. The study employed a Research and Development (R&D) design using the Four-D model, which consists of the define, design, develop, and disseminate stages. The game is designed to support learning of integer operations (addition, subtraction, multiplication, and division) through interactive challenges, gradually increasing levels of difficulty, immediate feedback, and appealing visuals. The results indicate that “Quick Count Math” meets the criteria of validity, practicality, and effectiveness. Expert review yielded validity scores of 85% for media aspects and 100% for content aspects, both categorized as very high. In addition, the game was reported to be easy to use by students and was effective in improving their understanding and learning outcomes on the integer topic, with an effectiveness score of 86%. These findings suggest that “Quick Count Math” can serve as an engaging and effective alternative digital medium for teaching mathematics in seventh-grade junior high school classes and contribute to the literature on game-based mathematics learning by offering a validated design that can be adapted to other topics and grade levels.